Conclusion: what is the transformative relationship between tourism and technology? - Liasidou, Sotiroula; Pipyros, Kosmas (My University, 2025)
Purpose: The thematic issue purposed explored the transformative relationship between tourism and technology from various perspectives. Design/methodology/approach: The thematic issue presents various methodologies that examine each topic. Each topic deals with an important issue of tourism and technology and provides an in-depth understanding of the interrelationship. Findings: The integration of technology in the tourism sector has significantly transformed several aspects, including customer and supplier behaviour, business operations, destination assessment, safety and education. Emerging technologies, like artificial intelligence, are reshaping the tourism industry by creating new opportunities for innovation and engagement. The industry’s primary challenge is to utilize these technologies wisely, ensuring they do not replace the concept of hospitality or the exceptional services that humans can offer. Originality/value: By providing diverse methodologies and perspectives, it highlights the multifaceted nature of the relationship between tourism and technology, thereby contributing original insights into how digital innovations are influencing traveller behaviours, destination marketing and operational efficiencies in the sector. The inclusion of case studies and empirical research enriches the discourse, enabling stakeholders such as policymakers, practitioners and researchers to better understand the implications of this transformative relationship and to adopt strategies that force technological advancements for sustainable tourism development.
Keywords: Big data analytics; Smart destinations; Technology; Tourism; Artificial intelligence; Digital innovation; Digital skills; Cybersecurity